Mein Kampf - Hitler, Adolf 1889-1945 (Crescentbooks in association with Fingerprint! Publishing, 2017)
Mein Kampf, the autobiography of Adobe Hitler, provides a peek into the mind of a man who literally single-handlely managed to change the course of history, wouding the psyche of a people for generations to come and marring the memories of a race for all the time